Green Communication and Networking Second International Conference, GreeNets 2012, Gandia, Spain, October 25-26, 2012, Revised Selected Papers - Mauri, Jaime Lloret; Rodrigues, Joel J. P. C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the Second International Conference, GreeNets 2012, held in Gaudia, Spain, in October 2012. The 11 revised full papers presented were carefully selected and reviewed. These papers represent 23.68% of the submissions and cover topics such as communications and networking, energy-efficient network architecture and protocols, systems and technologies, and energy-efficient management.
Carrier-Grade Networks toward the Future -NGN and Its Issues -- A Rendezvous Mobile Broker for Pub/Sub Networks -- Router Power Consumption Analysis: Towards Green Communications -- RDAP: Requested Data Accessibility Protocol in Vehicular Sensor Networks -- An Adaptive Cross-Layer Approach for Energy-Efficient and QoS-Constrained Multimedia Transmission over Wireless Channels -- Evaluation of Voltage Stabilization on a SmartGrid Simulation System -- Capacity Planning for Enterprise Green Communications -- Energy Consumption of Wireless Network Access Points -- Astroparticle Physics and Green Communication and Networking -- Exploiting SCTP Multistreaming to Reduce Energy Consumption of Multiple TCP Flows over a WLAN -- A Metropolitan-Scale Testbed for Heterogeneous Wireless Sensor Networks to Support CO2 Reduction.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Engineering economy; Computer Science; Computer Communication Networks; Computers and Society; System Performance and Evaluation; Energy Economics